Mechanisms of mitochondrial dysfunction in ovarian aging and potential interventions - Ju, Wenhan; Zhao, Yuewen; Yu, Yi; Zhao, Shuai; Xiang, Shan; Lian, Fang (Frontiers in Endocrinology, 2024)
Mitochondria plays an essential role in regulating cellular metabolic homeostasis, proliferation/differentiation, and cell death. Mitochondrial dysfunction is implicated in many age-related pathologies. Evidence supports that the dysfunction of mitochondria and the decline of mitochondrial DNA copy number negatively affect ovarian aging. However, the mechanism of ovarian aging is still unclear. Treatment methods, including antioxidant applications, mitochondrial transplantation, emerging biomaterials, and advanced technologies, are being used to improve mitochondrial function and restore oocyte quality. This article reviews key evidence and research updates on mitochondrial damage in the pathogenesis of ovarian aging, emphasizing that mitochondrial damage may accelerate and lead to cellular senescence and ovarian aging, as well as exploring potential methods for using mitochondrial mechanisms to slow down aging and improve oocyte quality.